Actuality of ensuring of consumption safety in the process of the European integration of Ukraine - Antoniuk, Katerina (Management and Entrepreneurship: Trends of Development, 2019)
Рurpose. The substantiation of the need to ensure the safety of consumption as a precondition for sustainable development and economic security of the state, is becoming more urgent in the context of the current global challenges, as well as in the process of European integration of Ukraine. Methods. The theoretical and methodological basis of the research is formed by the fundamental positions of the theories of global and national economy. To ensure the conceptual integrity of the study such methods as theoretical generalization, comparison, dialectics, analysis and systematization, institutional analysis, desk research, are used. Results. The urgency of solving the problem of ensuring the safety of consumption as an integral part of sustainable development in the global dimension and, in particular, in the process of European integration of Ukraine, is substantiated. The synergistic effect of development of the national economy as a result of the integrated interaction of society, enterprise and the state is hypothesized. The key manifestations of it should be: the formation of a model of safe consumption in society, creation of conditions for modernization of entrepreneurial activity in the context of the criterial restrictions of consumption safety, improvement of institutions for ensuring consumption safety on different levels of the system hierarchy. The importance of the results of the research for socio-economic development of the country is proved and directions of their practical implementation are determined.